Liberty : incorporating four essays on liberty - Berlin, Isaiah, 1909-1997; Hardy, Henry; Harrison, Ian, 1965-; Oxford University Press (Oxford : Oxford University Press, 2002)
"Liberty is a revised and expanded edition of a modern classic of liberalism, Four Essays On Liberty, regarded by Isaiah Berlin as his most important book, and constantly discussed since its publication in 1969. Irving Howe described it in Harper's as 'an exhilarating performance - this, one tells oneself, is what the life of the mind can be'." "Berlin's editor Henry Hardy has told the story of the book's genesis, revised the text, identified sources, incorporated a fifth essay that Berlin had wanted to include, and added three further pieces, so that Berlin's principal statements on liberty are now gathered together. Three appendices drawn from Berlin's unpublished papers help us to understand the core of personal conviction from which his writings sprang. A guide by Ian Harris to the huge literature stimulated by Berlin's ideas completes the volume."--Jacket
-- Introduction ---- Political Ideas in the Twentieth Century --- Historical Inevitability --- Two Concepts of Liberty --- John Stuart Mill and the Ends of Life --- From Hope and Fear Set Free --- Other Writings on Liberty --- Liberty --- The Birth of Greek Individualism --- Final Retrospect --- Autobiographical Appendices --- The Purpose Justifies the Ways --- A Letter to George Kennan --- Notes on Prejudice --- Berlin and his Critics by Ian Harris
"Four Essays on Liberty issued as an Oxford University Press paperback 1969. Liberty published in hardback and paperback 2002"--Title page verso
Includes bibliographical references and index
Keywords: Berlin, Isaiah, -- 1909-1997.; Liberty; Liberalism